2007
DOI: 10.1074/jbc.m701797200
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Cbl to a Phospholipase Cγ1-docking Site on Platelet-derived Growth Factor Receptor β Provides a Dual Mechanism of Negative Regulation

Abstract: Ubiquitin conjugation to receptor tyrosine kinases is a critical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 65 publications
2
28
0
Order By: Relevance
“…We found that cells, both normal human fibroblasts (AG1523) and glioblastoma cells (U251MG) lacking c-Cbl and Cbl-b had a stronger chemotactic response toward PDGF compared with control cells, partially consistent with a previous study where a similar effect was seen by cells lacking only c-Cbl (5). Previous studies have shown that the effect of c-Cbl overexpression on PDGF-induced proliferation depends on the passage number of the clone (4), suggesting that the cell adapts to continued c-Cbl overexpression.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We found that cells, both normal human fibroblasts (AG1523) and glioblastoma cells (U251MG) lacking c-Cbl and Cbl-b had a stronger chemotactic response toward PDGF compared with control cells, partially consistent with a previous study where a similar effect was seen by cells lacking only c-Cbl (5). Previous studies have shown that the effect of c-Cbl overexpression on PDGF-induced proliferation depends on the passage number of the clone (4), suggesting that the cell adapts to continued c-Cbl overexpression.…”
Section: Discussionsupporting
confidence: 78%
“…c-Cbl overexpression has been shown to lead to enhanced PDGFR␣ and ␤ ubiquitination and degradation as well as reduced PDGF-dependent proliferation and survival (4,5). The Cbl family consists of c-Cbl, Cbl-b, and Cbl-c (6).…”
mentioning
confidence: 99%
“…The E3 ubiquitin ligase, c-Cbl, is activated after PDGF stimulation and associates with phosphorylated PDGFR␤ (21,22). This in turn leads to PDGFR␤ ubiquitination, internalization via the clathrin-mediated pathway, and lysosomal degradation negatively regulating PDGFR␤ signaling and cell proliferation (21).…”
Section: Discussionmentioning
confidence: 99%
“…However, our data suggest that in contrast with F-actin assembly, c-Cbl does not mediate SLAP mitogenic inhibition. Therefore, c-Cbl may use distinct mechanisms for PDGFR association and ubiquitination (Reddi et al, 2007). Thus, we propose that SLAP dictates c-Cblspecificity towards PDGFR signalling.…”
Section: Slap Associates With C-cbl and Affects Rac Activationmentioning
confidence: 99%